Dyeability of SeaCell (R) active fabrics with reactive dyes by using of ultrasonic energy - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2012)
This paper presents a dyeing technique for the SeaCell (R) active fabrics that are dyed with reactive dyes in the presence of ultrasonic energy. 1.22 g/cm(2) of weight of 100% SeaCell (R) active fabrics made of herringbone pattern were used for this study. Three reactive dyes (blue, red and yellow) were chosen for the dyeing methods; the dyeing process was carried out at 60 degrees C for 60 minutes and with the liquor ratio of 40:1. The dyeing kinetics were studied along with their dyeing rates, colour yield, CIELab values, washings fastness, colour fastness to dry and wet rubbing tests. It has been observed that the use of ultrasonic energy in reactive dyeing of SeaCell (R) active fabrics have a considerable effect on the fixation of dyes and have a good colour yield.
Keywords: SeaCell active; ultrasonic energy; dyeability; reactive dye; dyeing rate; colour strength; fastness properties; colour measurement; COTTON